Inovasi Administrasi Madrasah Berbasis Digital: Studi di MAN 1 Bungo pada Era Society 5.0 - Yeni Aulia; Siti Khamim; Ulfa Adilla; Sugeng Kurniawan; Novita Nurul Hidayah; Sriani Sriani (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
This study examines digital-based madrasah administrative innovations at MAN 1 Bungo in responding to challenges while capitalising on opportunities in the Society 5.0 era. The study is motivated by the increasing demand for digital transformation in the management of Islamic educational institutions, aimed at improving the effectiveness, efficiency, and transparency of administrative services. The research employed a qualitative approach using a single case study design. Data were collected through observation, in-depth interviews, and documentation, involving the madrasah principal, educational staff, and teachers as primary informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was tested through source and method triangulation. The findings indicate that digital administrative innovations at MAN 1 Bungo have been implemented through the use of an academic information system, the digitisation of archives, and the utilisation of various online applications for managing student data, personnel records, and other administrative services. These implementations have produced positive impacts including increased work efficiency, easier access to information, transparency of management, and improved service quality for stakeholders. However, several challenges remain such as limited digital competence among educational staff, uneven technological infrastructure, and resistance to change. The study concludes that the digitisation of madrasah administration is an inevitable necessity in the Society 5.0 era and requires policy support, enhanced human resource competencies, and strengthened technological infrastructure. A sustainable and adaptive development strategy is needed to realise modern, effective, and competitive madrasah governance grounded in Islamic values.